Peripherally and non-peripherally tetra-HBME (4-hydroxybenzyl methyl ether) substituted metal-free and zinc(II) phthalocyanines: Synthesis, characterization, and investigation of photophysical and photochemical properties - Gunsel, Armagan; Beylik, Sevde; Bilgicli, Ahmet T.; Atmaca, Goknur Yasa; Erdogmus, Ali; Yarasir, M. Nilufer (ELSEVIER SCIENCE SA, 2018)
This paper reports on the synthesis and characterization of non-peripherally and peripherally tetrasubstituted metal-free and zinc(II) phthalocyanines functionalized with the phenolic compound 4-hydroxy-benzyl methyl ether (HBME). Synthesized compounds have been characterized by elemental analysis, FT-IR, H-1 NMR, C-13 NMR, MALDI-MS and UV-Vis spectral data. Besides, spectral, photophysical (fluorescence quantum yields and lifetimes) and photochemical (singlet oxygen generation and photodegradation under light irradiation) properties of newly synthesized phthalocyanines were investigated in DMF solution. We obtained very high singlet oxygen quantum yields as 0.86, 0.91, suggesting its potential as photosensitizer in PDT treatment. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; Synthesis; Zinc phthalocyanines; Photochemistry; SINGLET OXYGEN; HUMAN-DISEASE; PHOTOSENSITIZERS; Chemistry